O modernismo no estilo musical tardio de Gabriel Fauré: aspectos estilísticos e formais do Primeiro Movimento do Deuxième Quintette pour Piano et Cordes Op.115 - Marun, Nahim (Escola de Música da UFMG, 2010)
Analysis of Gabriel Fauré's late musical style, with focus on the harmony, counterpoint, rhythm and formal structure of the First Movement of the Deuxième Quintette pour Piano et Cordes Op. 115.

Análise dos aspectos estilísticos da última fase composicional de Gabriel Fauré, focando sobre aspectos harmônicos, contrapontísticos, rítmicos e formais encontrados no Primeiro Movimento do Deuxième Quintette pour Piano et Cordes Op.115.
The modernism in the late Gabriel Fauré's musical language: stylistic and formal features of the First Movement of the Deuxième Quintette pour Piano et Cordes Op.115
Keywords: Gabriel Fauré; musical analysis; musical style; chamber music; musical performance; Gabriel Fauré; análise musical; estilo musical; música de câmara; interpretação musical